Higher Physical Activity Level Improves Leptin Concentrations in Spinal Cord Injury Subjects - Ramkrapes, Ana Paula B.; Duft, Renata G.; Bonfante, Ivan L. P.; Mateus, Keryma C. S.; Trombeta, Joice C. S.; Rodrigues, Bruno; Chacon-Mikahil, Mara Patrícia T.; Tanhoffer, Ricardo A.; Cavaglieri, Claudia R. (BioMed research international, 2021)
The present study was designed to compare the body composition and indicators of chronic inflammatory grade, such as leptin, adiponectin, and resistin concentrations in irregularly active and active SCI subjects. Thirty-two male subjects participated in this study. They were divided into three groups: able-bodied control irregularly active (control, n=11), irregularly active with SCI (SCI-IA, n=8), and physically active with SCI (SCI-PA, n=13). The enzyme-linked immunosorbent assay (ELISA) assessed serum concentrations of leptin, adiponectin, and resistin. All volunteers performed the maximum oxygen uptake (VO2max) test, 24 h total energy expenditure (TEE), and body composition by skinfold thicknesses. Leptin concentrations were higher in the SCI-IA group when compared to the other groups, while no significant differences were found between the SCI-PA and control cohorts. In addition, no significant differences were found among groups for serum adiponectin and resistin concentrations either. The SCI-PA group showed significantly higher values for TEE and VO2max when compared to the other groups. Percentages of body fat and circumference were decreased in the control and SCI-PA groups when compared to the SCI-IA cohort. Associations between leptin and cardiorespiratory capacity and anthropometric markers were also observed. Our findings highlight that the lack of physical activity in the SCI subjects leads to poor general physical fitness and higher levels of body adiposity, which may induce hyperleptinemia, an essential marker for cardiometabolic disorders.